MACROECONOMIC DYNAMICS AND COMMUNITY WELFARE: AN EMPIRICAL STUDY OF PURCHASING POWER IN MEDAN CITY - Basri, Hunny Lutpiah; Sugianto, Sugianto; Harahap, Muhammad Ikhsan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study analyzes the influence of key macroeconomic factors on community purchasing power as an important indicator of social and economic welfare in urban areas. Specifically, it examines the effects of Gross Regional Domestic Product (GRDP), inflation, and the Regional Minimum Wage on purchasing power in Medan City, Indonesia. Purchasing power reflects the community’s ability to meet basic and non-basic needs and plays a strategic role in sustaining social stability and improving living standards within urban society. The study employs a quantitative approach using multiple linear regression analysis based on secondary monthly data from 2019 to 2023 obtained from the Central Statistics Agency. The results show that inflation has a negative and significant effect on purchasing power, while GRDP and the Regional Minimum Wage have positive and significant effects. Simultaneously, the three variables significantly influence purchasing power, with an R-squared value of 0.691, indicating that 69.1% of the variation in purchasing power is explained by the model. These findings highlight the importance of inclusive economic growth, sustainable wage policies, and effective inflation control in strengthening community welfare. This study contributes to social and economic development discourse by providing empirical evidence to support public policies aimed at improving the purchasing power and well-being of urban communities.